O trabalho de representação na clínica psicanalítica: entre a ruptura e a reconstituição psíquica - Socha, Andréa (2018)
The idea of the work of representation interrupted by trauma – as considered in the light of the deadly effects of the death drives – and its presentation as a content encrusted in symptomatology lead us to the core of the problem discussed in this work. Beyond the space of representation, traumatic reminiscences take on the expression of a particular nature, where we find an important key for understanding the suffering the subject is currently going through. We need to ask whether reminiscences that emerge within the analytical framework would be the starting point to gain new quality for lost traumatic experiences. In order to develop this question, three situations extracted from clinical practice illustrate and guide the investigation of the following axes: the first seeks to understand the nature of representational work and the conditions that impede its realization. The second seeks to reflect on the main and most archaic defensive mobilization in the face of trauma, that is, the splitting. And the third, finally, following the interaction between analyst and patient, intends to consider the possibility to work on the transformation of raw experiences into that which can be symbolized